Asymmetric synthesis of 3-aminodihydrocoumarins via the chiral guanidine catalyzed cascade reaction of azlactones. Issue 1 (26th September 2017) - Ruan, Sai; Lin, Xiaobin; Xie, Lihua; Lin, Lili; Feng, Xiaoming; Liu, Xiaohua
Abstract : A new asymmetric preparative method of 3-aminodihydrocoumarins via reactions of azlactones and 2-nitrovinylphenols using chiral bifunctional guanidine catalysts. Abstract : A highly efficient bifunctional guanidine catalyst was developed for the asymmetric cascade reaction between 2-nitrovinylphenols and azlactones. A wide variety of 3-aminodihydrocoumarin derivatives could be obtained in high yields (up to 99% yield) with excellent enantioselectivities (up to 99% ee) and diastereoselectivities (>19 : 1 dr).